Efeitos da deficiência ou suplementação de zinco sobre a hepatocarcinogênese química em camundongos - Romualdo, Guilherme Ribeiro [UNESP] (2016)
Zinc is required for a wide range of enzymes and transcription factors involved in DNA repair, antioxidant defense and cell proliferation. Inadequate zinc intake could impair these functions, predisposing to the development of human diseases. This study evaluated whether dietary zinc deficiency or supplementation alter early chemically-induced mouse hepatocarcinogenesis. Male Balb/C mice received a single dose of diethylnitrosamine (DEN, 50 mg/Kg) at postnatal day (PND) 15 as an initiating agent for hepatocarcinogenesis. At PND 28, animals were allocated into three groups (n=13/group) and were fed AIN-93G diet containing different concentrations of zinc: adequate zinc (35 mg/Kg diet), zinc deficiency (3 mg/Kg diet) or zinc supplementation (180 mg/Kg diet). Also, 2-acetylaminefluorene (2-AAF, 0.02%) was incorporated in all experimental diets as a promoting agent for hepatocarcinogenesis. Mice were euthanized at 12 or 24 weeks after introducing the experimental diets. Blood and liver samples were collected to perform Comet Assay. Other liver fragments were sampled for histopathological, morphometrical and immunohistochemical analyses, western blotting and antioxidant profiling. Zinc deficiency decreased Nrf2 expression and reduced glutathione (GSH) levels and increased NFκB, p53 expression and the number of preneoplastic altered hepatocyte foci (AHF) per cm² at week 12. In addition, zinc deficiency decreased GSH levels and increased 2-AAF-induced genotoxicity (peripheral blood and liver), cell proliferation into AHF and AHF size at week 24. In contrast, zinc supplementation increased GSH levels and Glutathione Peroxidase (GPx) activity and decreased 2-AAF-induced genotoxicity (blood) and β-catenin expression at week 12. Besides, zinc supplementation increased GSH levels and GPx, superoxide dismutase, and catalase activity at week 24. The findings indicate that zinc deficiency promotes early chemically-induced mouse hepatocarcinogenesis while zinc supplementation enhances hepatic antioxidant defense.